Comparative evaluation of aircraft joint stiffness between intermediate and high level of detail models - Santos , Marco Tulio dos; Greco, Marcelo (Acta Scientiarum. Technology, 2024)
The present work aims to compare results in aircraft joints, focusing on spar and skin regions, considering two levels of detail to understand the differences in the structural response using different types of modeling (numerical and semi-amalytical Rutman approach). Several studies were already performed to obtain the correct understanding of how actual loads are distributed through the joints. Finite Element Analysis modeling made using Nastran software were performed here. The study has shown the differences between the models analyzed by comparing the stiffness of the fasteners at the specific region analyzed. Results indicate good agreement between models for translational stiffness and more significant differences for rotational stiffness. The finite elements model with high level of detail presents larger rotational stiffness when compared with the Rutman approach.